1994
DOI: 10.1111/j.1476-5381.1994.tb13151.x
|View full text |Cite
|
Sign up to set email alerts
|

Actions of two new antagonists showing selectivity for different sub‐types of metabotropic glutamate receptor in the neonatal rat spinal cord

Abstract: 1 The presynaptic depressant action of L-2-amino-4-phosphonobutyrate (L-AP4) on the monosynaptic excitation of neonatal rat motoneurones has been differentiated from the similar effects produced by (1S,3R)-1-aminocyclopentane-1,3-dicarboxylate ((1S,3R)-ACPD), (1S,3S)-ACPD and (2S,3S,4S)-u-(carboxycyclopropyl)glycine (L-CCG-I), and from the postsynaptic motoneuronal depolarization produced by (lS,3R)-ACPD, by the actions of two new antagonists, a-methyl-L-AP4 (MAP4) and a-methyl-L-CCG-I (MCCG). Such

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(63 citation statements)
references
References 21 publications
4
58
1
Order By: Relevance
“…There is evidence showing that 1S,3R-1S,3R-ACPD does interact with mGluR4 (Thoreson and Miller, 1994;Flor et al, 1995); however, a form of 1S,3R-ACPD-induced presynaptic depression involves a component that is not mediated by the L-AP4 receptor (Cahusac, 1994;Jane et al, 1994;Lovinger and McCool, 1995). Thus, whether 1S,3R-ACPD and L-AP4 act on the same or distinct receptors to suppress synaptic transmission to PMNs remains unclear and requires further analysis.…”
Section: Possible Mechanism and Role Of Multiple Actions Of Mglurs Inmentioning
confidence: 99%
“…There is evidence showing that 1S,3R-1S,3R-ACPD does interact with mGluR4 (Thoreson and Miller, 1994;Flor et al, 1995); however, a form of 1S,3R-ACPD-induced presynaptic depression involves a component that is not mediated by the L-AP4 receptor (Cahusac, 1994;Jane et al, 1994;Lovinger and McCool, 1995). Thus, whether 1S,3R-ACPD and L-AP4 act on the same or distinct receptors to suppress synaptic transmission to PMNs remains unclear and requires further analysis.…”
Section: Possible Mechanism and Role Of Multiple Actions Of Mglurs Inmentioning
confidence: 99%
“…( (MSPG) and (RS)-ca-methyl-4-phosphonophenylglycine (MPPG) were synthesized as described previously Jane et al, 1994;Kemp et al, 1994b). (2S,1'R,2'R,3'R)-2-(2',3'-dicarboxycyclopropyl)-glycine (DCG-IV) was kindly provided by Dr Y. Ohfune (Tokyo). All drugs were made up as stock solutions, dissolved in equimolar NaOH at a concentration of at least 100 times the final concentration and were stored in frozen aliquots.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 It has been suggested that Group II mGluRs play an inhibitory role. 9 It has also been reported that the peptide neurotransmitter N-acetylaspartylglutamate (NAAG; reviewed in Neale et al) 10,11 is released from spinal cord cells by depolarizing stimuli and selectively activates mGluR3. 12 Intrathecal administration of NAAG peptidase inhibitors produces an analgesic effect in both inflammatory pain models and in neuropathic pain models.…”
Section: Conclusion : Les Agonistes α-2 Produisent Un Effet Analgésiqmentioning
confidence: 99%